Ammonium tolerance and toxicity of Actinoscirpus grossus - A candidate species for use in tropical constructed wetland systems - Narumol Piwpuan (2018)
Actinoscirpus grossus, a native species in tropical wetlands of South-East Asia, North Australia and the Pacific islands, has been reported to perform well in experimental scale constructed wetland (CW) systems. However, little is known about how high NH4+ concentrations prevailing in wastewater affect growth and performance of this species. We examined growth, morphological and physiological responses of A. grossus to NH4+ concentrations of 0.5, 2.5, 5, 10 and 15mM under hydroponic growth conditions. The relative growth rates (RGR) of the plants were highest at 2.5mM NH4+ but significantly reduced at 10 and 15mM NH4+. The roots of the plants were stunted and produced subepidermal lignified-cell layers at exposure to 10 and 15mM NH4+. The photosynthetic rates did not differ between treatments (average A n =21.3±0.4μmolCO 2 m -2 s -1 ) but the photosynthetic nitrogen and carbon use efficiency (PNUE and PCUE) were significantly depressed at 10 and 15mM NH4+ treatments. The concentration of NH4+ in the roots, but not in the leaves, reflected the NH4+ concentration in the growth medium suggesting that the species is unable to regulate the NH4+ uptake. The high root respiration rates in concert with high tissue NH4+ and declined C/N ratio at 10 and 15mM NH4+ suggest that the NH4+ assimilation occurs primarily in the roots and the plant has inadequate C-skeletons for NH4+ assimilation and exudation at high NH4+ concentration in the external solution. The concentrations of mineral cations were generally reduced and the root membrane permeability increased at high external NH4+ concentrations. Our study shows that A. grossus tolerates NH4+ concentrations up to 5mM which is characteristic of most types of wastewater. Hence, A. grossus is a good native candidate species for use in CW systems in tropical and subtropical climates in South-East Asia, North Australia and the Pacific islands. © 2014 Elsevier Inc.